Liberdade e democracia: fundamentos e fins do desenvolvimento na perspectiva de Amartya Sen - COIMBRA, Fabio (2015)
The general objective of this research is to understand the importance of freedom (freedom of choice) and democracy for the construction of the Theory of the Development (in its human perspective) in the works of the Indian philosopher and economist Amartya Sen. Taking into consideration the results that are aimed to be reached, an analytical and hermeneutics reading and the comparison of selected texts will be held as a methodological strategy through all this study. A brief presentation of the Theory of the Development as freedom will be carried out taking debates and theories that were formed around the issue in the context of the development that followed the Second World War as a starting point for reflection. The relevance of Ethics in promoting development will be investigated arguing that its relevance increases when Ethics and Economics are joined, and decreases when they separate apart. The critics of Amartya Sen to the traditional concept of development that identified it to factors such as the increase in the GNP (Gross National Product) and industrialization will be presented, as well as the perspective of freedom as a means and a goal of development. In this context, it is defended that the development thought by Sen can be understood as a process of eliminating the privations that limit the choices and the capabilities of individuals restricting their freedom to live the life they wish and value. The extension of choices will appear then as the real goal of human development. The perspective of democracy trying to understand its intrinsic importance, its protective role and its constructive importance will be discussed. In this regard, it will be argued that the practice of democracy means giving citizens the opportunity to participate in power so that they can participate in Politics. This participation enables them to be agents. Someone who according to Sen (2010, p. 34): "acts and brings about change and whose achievements can be judged according to their own goals."